The regulation of education in the First Republic (Research, Society and Development, 2018)
During the First Republic period, many were the political, economic and social transformations experienced by Brasil and, consequently, by the state of Rio Grande do Norte. At the moment, the public education will also undergo profound changes in its structure, these begin with the reforms foreseen by the Educational Legislation. Thus, this article aims to analyze the Educational Legislation to understand the State's performance in the construction of school culture through the regulation of teaching in the period from 1989 to 1930. For the accomplishment of this research, the method of analysis Based on the document design provided by Jacques Le Goff (1990). For this, in relation to historical sources, this Research is based on the legislative production of the state of Rio Grande do Norte, regarding public education. In studying the history of education, Stamatto (2012) conceives the importance of legislation as a historical source, because these documents allow the understanding of the implementation and changes in educational policies. Legislation consolidates, according to Thompson (1987), as an important instrument of mediation and reinforcement of class relations, while at the same time acting ideologically as legitimating these relations. In the legislation are the pretensions regarding the constitution of the own society and its institutions, through a complex and contradictory relation. The first Potiguar educational law of the Republican era was sanctioned on May 6, 1892, from then on, many governmental interventions in teaching ensued. These documents addressed several themes, such as: hierarchization / organization of teaching; The teaching material to be used; Construction of school buildings; Hygiene; The curriculum grid; Inspection; The creation of School Groups; Among other determinations. Finally, based on the study carried out, it can be stated that the State acted decisively in the regulation of public education, in order to consolidate the school culture in Rio Grande do Norte, in accordance with the models proposed by Julia (2001).